Emergency open-heart surgery in infancy using hypothermia and inflow occlusion - Aytaç, Aydın; Tuncalı, Tahsin; Yurdakul, Yurdakul; Saylam, Argun; Bakay, Cihat (The Turkish Journal of Pediatrics, 1973)
A case of severe pulmonary stenosis in a 10-month old infant that was treated by inflow occlusion and hypothermia is presented. The importance of this technique in infantile cardiac surgery as a life-saving measure is emphasized.